Well-Defined Cyclohexene Oxide Mid-Chain Functional Polystyrene Macromonomer: Synthesis, Characterization and Photoinitiated Cationic Homo- and Copolymerization - Degirmenci, Mustafa; Acikses, Aslisah; Genli, Nasrettin (Wiley-V C H Verlag Gmbh, 2010)
In this article, we present the results of a study of the preparation of a cyclohexene oxide (CHO) mid-chain functional macromonomer via ATRP of styrene (St) and epoxidation on work-up with 3-chloroperoxybenzoic acid. The ATRP initiator, Br-CH-Br, was synthesized by the condensation of 3-cyclohexene-1,1-dimethanol with 2-bromopropanoyl bromide. The ATRP of St with Br-CH-Br and Cu(I)/bpy yielded well-defined polystyrene with a cyclohexene mid-chain group (PSt-CH-PSt). Epoxidation of the PSt-CH-PSt was performed using 3-chloroperoxybenzoic acid. GPC, IR and H-1 NMR analyses revealed that a low polydispersity macromonomer of polystyrene with CHO functionality at the mid-chain (PSt-CHO-PSt) was obtained. The photoinduced cationic polymerization of PSt-CHO-PSt yielded comb-shaped and graft copolymers.
Keywords: atom transfer radical polymerization (ATRP); copolymerization; functionalization of polymers; macromonomers; polystyrene (PSt)